Oral Hygiene Practices, Treatment Needs and Barriers to Dental Care Among Adolescents Attending Special Education Schools in Shah Alam, Selangor, Malaysia - Nor Wira, Nur Hafizah; Mamat, Noraida; Rohani, Maryani Mohamed; Kamarudin, Aimi; Anis, Sofia (Journal of Dentistry Indonesia, 2025)
Objective: This study aimed to evaluate the oral health practices, status, and treatment requirements of adolescents with special healthcare needs attending special education schools in Selangor, Malaysia. The adolescents’ parents perceived challenges to oral healthcare were also established. Methods: The current study employed a cross-sectional approach involving 131 adolescents with varying special needs. The participants were between 13 and 18 years old and fulfilled the pre-determined inclusion criteria. The participants’ parents supplied information on sociodemographic, oral health practices, and possible obstacles to dental care through an online survey form. The oral examination on decay, missing, and filled teeth (DMFT), simplified oral hygiene index (OHI-S), and treatment requirements were performed in the school with teachers in attendance. The chi-square test was then conducted during statistical analyses. Results: Most adolescents examined in this study demonstrated good oral hygiene, recording 0.79 ± 1.49 and 0.73 ± 0.4 mean DMFT and OHI-S scores, respectively. A majority of the participants also reported brushing their teeth more than once daily, while approximately 93.9% employed fluoridated toothpaste. A majority of the participants required oral prophylaxis and restorative treatment. Nevertheless, the most significant barriers perceived by the parents or caregivers were time constraints to bring their child to dental clinics and the child's dental anxiety. The present study found no association between barriers to dental care and dental treatment requirements. Conclusion: The results indicated no correlation between barriers to dental care and dental treatment requirements. The findings might be due to this study being conducted in an urban area in Malaysia. Consequently, a multi-centre study with a bigger sample size is recommended.